A140 INTEROBSERVER RELIABILITY OF THE PARIS CLASSIFICATION FOR SUPERFICIAL GASTROINTESTINAL TRACT NEOPLASMS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (21st February 2022) - Gupta, S; Seleq, S; Gimpaya, N; Khan, R; Scaffidi, M; Grover, S
Abstract: Background: The Paris classification is an international classification system that characterizes the morphology of superficial gastrointestinal tract neoplasms. Given its ability to predict the risk of submucosal invasion, this tool plays an important role in the preliminary endoscopic assessment of early gastrointestinal neoplastic lesions. Despite its international prevalence, there are no pooled reliability analyses to assess agreement amongst endoscopists using this classification system. Aims: To systematically review and meta-analyze the interobserver reliability (IOR) of the Paris classification system. Methods: We conducted a systematic review and meta-analysis according to the PRISMA recommendations. A comprehensive literature query was conducted on biomedical databases through December 2020. Studies were included if they quantitively evaluated the IOR of the Paris classification with at least 5 endoscopists participating in the study cohort. Two authors independently screened studies and abstracted data using an a priori designed data collection form. We pooled the results of studies which provided IOR with kappa statistics and confidence intervals using DerSimonian and Laird random effects models. Risk of bias was independently assessed by two study authors using the Guidelines for Reporting Reliability and Agreement Studies (GRRAS) tool. Results: From an initial 1541 studies, 5 were included in the qualitative review and 3 reported data that allowed for a quantitative analysis of the primary outcome, representing a total of 28 endoscopists. All three of these studies were high quality. The IOR for the Paris classification amongst all endoscopists was 0.541 (95% CI, 0.466–0.617). There was no significant improvement (p=0.551) in the IOR of the Paris classification system following an educational training intervention (pre-education pooled kappa, 0.498; 95% CI, 0.429–0.567 compared to post-education pooled kappa, 0.530; 95% CI, 0.451–0.608). Conclusions: Interobserver reliability of the Paris classification is moderate with no significant improvement following educational intervention. Funding Agencies: None